Global aphasia as a predictor of mortality in the acute phase of a first stroke - F F Oliveira; B P Damasceno (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To establish whether vascular aphasic syndromes can predict stroke outcomes. METHOD: Thirty-seven adults were evaluated for speech and language within 72 hours after a single first-ever ischemic brain lesion, in blind association to CT and/or MR. RESULTS: Speech or language disabilities were found in seven (87.5%) of the eight deceased patients and twenty-six (89.7%) of the twenty-nine survivors. Global aphasia was identified in eleven patients, all with left hemisphere lesions (nine mute; five deceased), consisting on a risk factor for death in the acute stroke phase (ρ=0.022). Age (z=1.65; ρ>0.09), thrombolysis (ρ=0.591), infarct size (ρ=0.076) and side (ρ=0.649) did not significantly influence survival. Absence of aphasia did not predict a better evolution, regardless of the affected hemisphere. Prevalence of cardiovascular risk factors was similar for all patient groups. CONCLUSION: Global aphasia in acute stroke can adversely affect prognosis, translated into impairment of dominant perisylvian vascular territories, with mutism as an important semiological element.